Motivasi Mahasiswa dalam Memilih Prodi PBA Jurusan Tarbiyah STAIN Samarinda - Abusyairi, Khairy (FENOMENA, 2015)
A quality of education can be achieved by implementing a quality learning. To improve its quality, STAIN Samarinda plans and evaluate its educational programs periodically to become an excellent distinguished higher institution in Kalimantan Timur. It is important to encourage the candidate of college students to choose STAIN Samarinda as their options to continue the study. This motivation deals with the prosperity of work, recommendation or suggestions of family and friends, perception of Arabic language program, appropriateness of interest and talents, ambitions, willingness, teachersâ qualifications, and sufficient information about the study program. This is a descriptive qualitative research design. The data were collected by using interview and documentation. The result of findings shows the studentsâ motivation in choosing the Arabic study program of STAIN Samarinda is to learn Arabic entuastically, fit to their ambitions, and linier to their former educational background.